2010
DOI: 10.1073/pnas.1002565107
|View full text |Cite
|
Sign up to set email alerts
|

X-ray structure and mechanism of RNA polymerase II stalled at an antineoplastic monofunctional platinum-DNA adduct

Abstract: DNA is a major target of anticancer drugs. The resulting adducts interfere with key cellular processes, such as transcription, to trigger downstream events responsible for drug activity. cisDiammine(pyridine)chloroplatinum(II), cDPCP or pyriplatin, is a monofunctional platinum(II) analogue of the widely used anticancer drug cisplatin having significant anticancer properties with a different spectrum of activity. Its novel structure-activity properties hold promise for overcoming drug resistance and improving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
119
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 40 publications
4
119
0
Order By: Relevance
“…Finally (state 3 to state 4), the transition base rotates to the canonical position of posttranslocation state, which allows full base pairing with the incoming NTP. The intermediate state's identity is consistent with previous translocation intermediate structures trapped either by α-amanitin or DNA damage (13,37), in which the TN base is located on top of the BH.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Finally (state 3 to state 4), the transition base rotates to the canonical position of posttranslocation state, which allows full base pairing with the incoming NTP. The intermediate state's identity is consistent with previous translocation intermediate structures trapped either by α-amanitin or DNA damage (13,37), in which the TN base is located on top of the BH.…”
Section: Resultssupporting
confidence: 74%
“…To proceed to the next NAC, Pol II must translocate from a pretranslocation state, in which the active site is still occupied by the newly added nucleotide at 3′-RNA, to a posttranslocation state. During translocation, the template DNA and RNA must move by exactly one register, once again creating a free insertion site (i site) (1,2,5,(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…A structural analysis of RNA pol II stalled at a site-specific pyriplatin lesion suggested that, by increasing the steric bulk of the N-heterocyclic ligand, it might be possible to increase transcription inhibition and consequential cytotoxicity [32]. From a panel of different N-heterocyclic ligands, Am, a series of complexes having the formula cis-[Pt(NH 3 ) 2 Cl(Am)] + was prepared [33].…”
Section: Monofunctional Platinum Anti-cancer Agents (A) Pyriplatin: Rmentioning
confidence: 99%
“…Aligning the structures of 5caC-paused pol II elongation complex with several recent bulky DNA lesionarrested complexes reveals new insights into pol II pausing and arrest upon DNA modifications/ lesions. 12,17,26,29 Intriguingly, the iC1 transition template base in these 5caC-paused or bulky DNA lesion-arrested structures are all accommodated "above the bridge helix," representing a common translocation checkpoint for a variety of endogenous DNA modifications and DNA lesions. 12,17,26,29 Intriguingly, the similar "above the bridge helix" translocation intermediates are also observed for non-damaged pausing and arrest complexes revealed by the structures of the a-amanitinarrested pol II complex 5,30 and the E. Coli RNAP pausing complex.…”
mentioning
confidence: 99%
“…12,17,26,29 Intriguingly, the iC1 transition template base in these 5caC-paused or bulky DNA lesion-arrested structures are all accommodated "above the bridge helix," representing a common translocation checkpoint for a variety of endogenous DNA modifications and DNA lesions. 12,17,26,29 Intriguingly, the similar "above the bridge helix" translocation intermediates are also observed for non-damaged pausing and arrest complexes revealed by the structures of the a-amanitinarrested pol II complex 5,30 and the E. Coli RNAP pausing complex. 31 Another interesting example is revealed by a recent structure of the RNA pol III elongation complex, 32 in which the undamaged template iC1 nucleobase adopts a similar "above the bridge helix" position.…”
mentioning
confidence: 99%